X-ray and multi-epoch optical/UV investigations of BAL to non-BAL quasar transformations. Issue 1 (8th October 2018) - ,; Brandt, W N; Anderson, S; Hall, P B; Vivek, M; Filiz Ak, N; Grier, C J; Ahmed, N S; Luo, B; Myers, A D; Rodríguez Hidalgo, P; Ruan, J; et al.
ABSTRACT: We report on an X-ray and optical/ultraviolet (UV) study of eight broad absorption line (BAL) to non-BAL transforming quasars atz ≈ 1.7–2.2 over 0.29–4.95 rest-frame years with at least three spectroscopic epochs for each quasar from the SDSS, BOSS, Gemini, and ARC 3.5 m telescopes. New Chandra observations obtained for these objects show that their values of αox and Δαox, as well as their spectral energy distributions, are consistent with those of non-BAL quasars. Moreover, our targets have X-ray spectral shapes that are, on average, consistent with weakened absorption with an effective power-law photon index ofΓ _eff=1.69^+0.25_-0.25 . The newer Gemini and ARC 3.5 m spectra reveal that the BAL troughs have remained absent since the BOSS observations where the BAL disappearance was discovered. The X-ray and optical/UV results in tandem are consistent with at least the X-ray-absorbing material moving out of the line of sight, leaving an X-ray-unabsorbed non-BAL quasar. The UV absorber might have become more highly ionized (in a shielding-gas scenario) or also moved out of the line of sight (in a wind-clumping scenario).